Pengaruh Celebrity Endorser dan Word of Mouth terhadap Keputusan Pembelian melalui Brand Awareness (pada Mie Aceh Kedai Kiko Jakarta) - Nur Chotimah; Rivera Pantro Sukma (Sekolah Pascasarjana Perbanas Jakarta, 2022)
The aim of this study was to determine the influence of celebrity endorser and word of mouth on purchasing decisions through brand awareness in Mie Aceh Kedai Kiko Jakarta. The population in this study were buyers to Kedai Mie Aceh Kiko Jakarta with 200 participants. The sampling technique used in this study is purposeful sampling. This study uses a quantitative descriptive method by conducting survey research based on data by distributing questionnaires to respondents and the analytical method used by the author in this study is path analysis. The author used a quantitative descriptive method that is by analyzing the data using IBM SPSS Statistics 26. The results show that Word of mouth has a significant effect on Brand awareness, Celebrity endorserhas a significant effect on Brand awareness, Word of mouth and Brand awareness has a significant effect on Purchase Decisions, but Celebrity endorserhas no significant effect on Purchase Decisions at Mie Aceh Kedai Kiko Jakarta. Celebrity endorsers have an indirect effect on purchasing decisions through Brand awareness with a contribution of 0.065. Word of mouth has an indirect effect on purchasing decisions through Brand awareness with a contribution of 0.182.